Pengaruh Gaya Kepemimpinan Dan Motivasi Terhadap Kinerja Karyawan Sardo Swalayan Kota Malang - M. Rahmad K; Abd Kodir Djaelani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine the effect of leadership style and work motivation on the performance of employees of Sardo Swalayan Malang. The analasis method used in this research is descriptive method with quantitative approach and multiple regression. The results of this study indicate that the leadership style variable has a positive and significant effect on employee performance and the motivation variable has a positive but not significant effect on the performance of employees of Sardo Swalayan Malang, this can be seen from the results of the study. T-test significant level of work motivation is 0.804> significant level α = 0.05, which means H0 is accepted and Ha is rejected. The results of multiple regression data analysis obtained are Y = 12,276 + 0,353 X1 + 0,038 X2 + 3,159. The results of this study indicate that the variables of leadership style and work motivation have a significant and simultaneous effect on the performance of employees of Sardo Swalayan Malang. Keywords: leadership style, motivation, employee performance